2001
DOI: 10.1002/mrc.973
|View full text |Cite
|
Sign up to set email alerts
|

13C PHIP NMR spectra and polarization transfer during the homogeneous hydrogenation of alkynes with parahydrogen

Abstract: Homogeneously catalyzed hydrogenations of unsaturated substrates with parahydrogen not only lead to strong polarization signals in 1 H NMR spectra, but also can give rise to strong heteronuclear polarization, especially if the hydrogenations are carried out in low magnetic fields. As a typical example, the polarization transfer from protons to carbon nuclei during the hydrogenation of alkynes is outlined for several substrates. In systems containing easily accessible triple bonds, e.g. phenylethyne or 3,3-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 14 publications
(22 reference statements)
0
45
0
Order By: Relevance
“…It could be shown that in systems containing easily accessible triple bonds (Table 12.5) (e.g., ethynylbenzene or 2,2-dimethylbutyne), a polarization transfer takes place to all carbon nuclei in the molecule. Accordingly, all 13 C resonances can be observed in NMR spectra recorded in situ with good to excellent signal-to-noise ratios (SNRs) using only a single transient [42]. This technique has made it possible to identify a Ru-based catalyst system, which yields E-alkenes via homogeneous hydrogenations of alkynes with central triple bonds, as opposed to the more conventional Z-alkenes that result from hydrogenation with Rh-based catalysts [47].…”
Section: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be shown that in systems containing easily accessible triple bonds (Table 12.5) (e.g., ethynylbenzene or 2,2-dimethylbutyne), a polarization transfer takes place to all carbon nuclei in the molecule. Accordingly, all 13 C resonances can be observed in NMR spectra recorded in situ with good to excellent signal-to-noise ratios (SNRs) using only a single transient [42]. This technique has made it possible to identify a Ru-based catalyst system, which yields E-alkenes via homogeneous hydrogenations of alkynes with central triple bonds, as opposed to the more conventional Z-alkenes that result from hydrogenation with Rh-based catalysts [47].…”
Section: General Aspectsmentioning
confidence: 99%
“…This frequently simplifies the assignment, thereby facilitating the interpretation of 13 C-NMR spectra of more complex molecules. The polarization phenomena occurring in the 13 C-PHIP-NMR spectra during the in-situ hydrogenation of various alkynes using the catalyst [Rh(cod)(dppb)] + in CDCl 3 at 5 bar of parahydrogen may serve as a characteristic example [42].…”
Section: Polarization Transfer To 13 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical example taken from Ref. [74], the polarization transfer from protons to 13 C nuclei during the hydrogenation of 3,3-dimethylbut-1-yne with para-hydrogen and [Rh(cod)(dppb)] + as catalyst is shown in Fig. 21.11.…”
Section: C-phip-nmrmentioning
confidence: 99%
“…Note the extremely high signal/noise ratio in the single shot spectrum, which is a measure for the strong signal enhancement obtained by PHIP (adapted from Ref. [74]). …”
Section: C-phip-nmrmentioning
confidence: 99%